탈지 정도에 대한 방청유-금속 계면의 영향성 평가 - 최원영(Wonyoung Choi); 김문수(Moonsu Kim); 유현석(Hyeonseok Yoo); 송연균(Yeongyun Song); 정용균(Yong-Gyun Jeong); 최진섭(Jinsub Choi) (Biuletyn Uniejowski, 2021)
The use of anti-corrosive oil (AC) is inevitable for production of industrial steels to prevent corrosion. The AC is degreased before application of steels, which crucially effects on final products, such as automobile, electricity etc. However, qualitative/quantitative evaluation of degreasing performance are steal insufficient. In this study, degreasing performance of anti-corrosive oil on steel have been studied through X-ray photon spectroscopy (XPS) and electrochemical impedance spectroscopy (EIS). Commercial automotive steels (AMS) are coated with 4 different anti-corrosive oils (namely AC1-AC4). In XPS, intensity of C1s peak remained after degreasing indirectly indicates incomplete degreasing. Thus, higher C1s peak intensity means less effective degreasing by degreasing agent. peak intensity of C1s peak shows opposite tendency of peak intensity of O1s. We found that EIS analysis is not applicable to mild steel (such as AMS1) due to corrosion during measurement. However, alloy steel can be fully analyzed by EIS and XPS depth profile.